Novel aspects of benzyne chemistry - Birkett, Michael Alexander (1994)
Chapter One describes attempts at utilising ortho-quinodimethanes in the synthesis of polycyclic ring systems, where construction of the the 1,4-elimination precursor could not be achieved. Additionally, several attempts were made to utilise the diradical behaviour which ortho-quinodimethanes are thought to possess, in similar annulative reactions. Unsuccessful attempts at generating furanyl- ,benzofuranyl- and benzenoid- derived diradical species, however, brought these particular studies to an end. The remainder of this thesis is devoted to studies that were made into developing new uses for benzynes in organic synthesis. Their discovery, general history and subsequent application is divided for convenience into three chapters; Chapter Two covers the discovery of these classic species, and approaches to these species which have been improved from the highly impractical methods which were originally developed. Chapters Three and Four give an overall review of the past and recently reported applications of benzynes in organic synthesis; Chapter Three covers the use of benzynes in nucleophilic couplings, whilst Chapter Four covers their application in cycloaddition reactions. Chapter Five describes preliminary studies that were made into developing new routes to polycyclic ring systems via the intramolecular Diels-Alder trapping of benzynes. After unsuccessful attempts at utilising the anthranilic acid route to benzynes, the remainder of the studies were concentrated on utilising the 1-aminobenzotriazole route to benzynes, a mild, efficient, yet relatively underexploited route. An improved synthesis of 7-methyl-1-aminobenzotriazole is described, as is the functionalisation of the methyl substitutent in the BOC-derivative via the formation of the dianion. However, 1,3-diene incorporation via this route was unsuccessful, due to difficulties in preparing suitable l,3-dienes. Chapter Six describes attempts at applying the metallation chemistry of BOC-protected 7-methyl-l-aminobenzotriazole to the synthesis of 2-substituted dihydrobenzofurans (n = 0) and chromans (n = 1) via the intramolecular trapping of benzynes by flanking hydroxyl functions, which were incorporated via the condensation of the dianion with aldehydes and epoxides respectively. Using H-bromosuccinimide as the reagent for benzyne generation, benzo-fused heterocycles were successfully generated in moderate yields, with bromine incorporation also being achieved (X =Br). Using lead (1V) acetate, simple dihydrobenzofurans (X=H) were obtaine4 in better yields. Excellent yields, in some cases virtually quantitative, were obtained using N-iodosuccinimide as the reagent, with the iodine substituent (X = I) being incorporated. The additional bonus of having the iodine substituent was highlighted by utilising iododihydrobenzofurans and chromans in subsequent coupling reactions. Overall, this thesis describes the advances made in increasing the role of benzynes in synthetic organic chemistry, providing novel metalation chemistry on the aminobenzotriazole ring system, and a novel annulative approach to valuable synthetic and potentially active species such as dihydrobenzofurans and chromans. Above all, this work illustrates that under certain suitable conditions, benzynes can serve as extremely efficient reactive intermediates in heterocyclic annulations.